INVESTIGATING MECHANISMS OF CANCER VACCINE-INDUCED TUMOR IMMUNITY AND AUTOIMMUNITY - Bernard, Dannie (My University, 2011)
INTRODUCTION: Pre-clinical and clinical data strongly support the feasibility of employing immunotherapy as a strategy to treat cancer.
METHODS: Using the B16F10 murine melanoma model, we have been investigating mechanisms of T cell-mediated antitumor immunity following immunization with dopachrome tautomerase (DCT), a melanoma-associated antigen.
RESULTS: In Chapter 2, we uncovered an interesting dichotomy whereby DCT-specific CD4+ T cell-mediated tumor protection and autoimmunity are dependent on IL-4/STAT-6 and IFN-g/STAT-4, respectively. Our data also revealed that this phenomenon is extrinsic of CD4+ T cell polarization.
To gain further insight into the targets recognized by CD4+ T cells, we conducted in Chapter 3 extensive CD4+ T cell epitope mapping experiments using overlapping peptide libraries. Interestingly, while we were able to identify “helper” epitopes within DCT that were required for maximal CD8+ T cell expansion, we were unable to identify “effector” epitopes responsible for tumor rejection. Further examination of the requirements for the generation of CD4+ T cell effector epitopes showed that post-translational modifications of the protein were involved.
In Chapter 4, we investigated the modest efficacy afforded by DCT immunization in the context of established B16F10 melanomas. Using intratumoral transcriptional analysis, we demonstrated that the vaccine rapidly promoted an IFN-g-dependent immunosuppressive state inside the tumor. Concurrent treatment with the immunomodulatory antibodies anti-4-1BB and anti-PD-1 effectively counteracted this tumor immunosuppression, resulting in complete regression of tumors and long-term survival in 70% of the mice.
CONCLUSIONS: The research described in this thesis sheds new light into the mechanisms by which vaccine-mediated CD4+ T cell responses participate to tumor rejection and autoimmunity. Moreover, our findings indicate that cancer vaccine-induced tumor immunosuppression significantly limits tumor regression, emphasizing the requirement of combinatorial approaches for successful cancer immunotherapy. Overall, our research offers new insight for future vaccine development.
Keywords: cancer immunotherapy; T cells; tumor immunity; autoimmunity; immune regulation; viral vectors; Immunity; Immunoprophylaxis and Therapy; Immunity